The Effects of Water Intake, Fruits and Vegetables Consumption, and Socio-Cultural on Obesity among Adolescents - Nita Aprilia; Didik Tantomo; Pawito Pawito; Bhisma Murti (Journal of Health Promotion and Behavior, 2018)
Background: The prevalence of obesity is increasing in the world, especially in Indonesia. Obesity can cause health problems, such as hyperinsulinemia, diabetes, cardiovascular disease, hypertension, immunological disorders, certain types of cancer, etc. This study aims to analyze the influence of consumption of water, fruit and vegetables and sociocultural views on the risk of obesity in senior high school adolescents.Subjects and method: This was a cross-sectional study conducted at 25 senior high schools in Banyuwangi, East Java, from March to April 2018. Samples of 225 students were selected using random sampling technique. The dependent variable was obesity. The independent variables were consumption of water, fruit and vegetables and socio-cultural views. The data were collected using questionnaires and analyzed using multilevel logistic regression.Results: Water consumption (b = -2.67; CI 95% = -3.77 to -1.58; p = <0.001), fruit and vegetables (b = -1.16; CI 95% = -1.88 to -0.44; p = 0.002), activity physical (b = -1.12; 95% CI = -2.08 to -0.15; p = 0.023) and socio-cultural views (b = -1.89; CI 95% = -2.72 to -1.05; p = <0.001) reduce risk of obesity . Genetic factors (b = 3.12; 95% CI = 1.98 to 4.26; p = <0.001) increase the risk of obesity. Senior high school has a contextual effect on the risk of obesity with ICC = 9.89%.Conclusion: The risk of obesity decreases with adequate consumption of water, consumption of enough fruits and vegetables, enough physical activity and living in a society with a socio-cultural outlook with a good diet. The risk of obesity increases with the presence of factors. SMA has a contextual influence on the risk of obesity in adolescents.Keywords: water, fruit and vegetables, socio-cultural views, obesityCorrespondence: Nita Aprilia. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir.Sutami No. 36 A, Surakarta, Central Java. Email: nitaapriliamelia@gmail.com. Mobile: +6283847987215.Journal of Health Promotion and Behavior (2018), 3(4): 279-289https://doi.org/10.26911/thejhpb.2018.03.04.08